Optical investigation of the electronic structure of alloys Сu-Fе - Vovchenko, V.V.; Staschuk, V.S.; Poperenko, L.V.; Lysiuk, V.O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
We investigate the optical properties of Cu-Fe alloys in a wide interval of concentrations (7.5–30 at. %) and in a wide spectral interval (0.25–7 µm). An additional absorption associated with interband electron transitions from localized states of impurities to the Fermi level has been revealed in the 0.98–1.9-eV spectral range. The energy bands in Cu-Fe alloys are almost undeformed and similar to copper ones, while the Fe impurity forms localized d-bands at a distance of about 1.0-1.6 eV from the Fermi level. For high impurity concentrations, the experimental optical conductivity spectra σ (hν) of the alloys are determined by a superposition of the spectra of Fe and the appropriate solid solution with the corresponding weight coefficients. The obtained experimental data allow one to calculate the density of states N (Е) which is related to the impurity band.